Two new annual fishes (Cyprinodontiformes: Rivulidae) unexpectedly discovered in the highlands of southern Brazil - Lanés, Luis Esteban Krause; Volcan, Matheus Vieira; Maltchik, Leonardo (Zootaxa, 2021)
Two new species of Austrolebias are described based on specimens collected from temporary pools located in natural grassland landscape within the Araucaria Forest domain at exceptionally high altitudes ( 1000 meters a.s.l.). Austrolebias botocudo sp. n. and Austrolebias nubium sp. n. occur, respectively, in drainages of upper rio Apuaê-Inhandava (upper rio Uruguay basin) and upper rio Taquari-Antas (upper rio Jacuí, Laguna dos Patos basin), in the Meridional Plateau of southern Brazil. Despite an intensive survey conducted in the area, only two populations of each species were recorded. Both new species occurs at altitudes that are among the higher recorded for species of the genus, and both are assigned to the subgenus Acrolebias. The new species described herein are easily distinguished for its congeners by the colour pattern of males, by presence of melanophores irregularly distributed in different parts of the body, contact organs cover the body and anal fins, position of fins related with vertebrae, by preopercular and mandibular series of neuromasts united, by a series of morphometric features and by larger maximum standard length. Austrolebias botocudo and A. nubium are distinguished from each other by colour pattern of males, length of contact organs in the flank and number of contact organs in scales of lateral line, dorsal profile of head, number of neuromasts in the preopercular + mandibular series, body depth in females, and by basihyal cartilage length. Additionally, we discuss the conservation status of the new species, and provided an identification key for the species of the subgenus Acrolebias.